Volume 6: Materials and Fabrication, Parts a and B 2008
DOI: 10.1115/pvp2008-61612
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Data Analysis Methodology for Estimating Reliability of Weld Flaw Detection, Location, and Sizing

Abstract: Recent advances in computer technology, internet communication networks, and finite element modeling and analysis capability have made it feasible for engineers to accelerate the feedback loop between the field inspectors of a structure or component for critical flaws by nondestructive evaluation (NDE) and the office engineers who do the damage assessment and recommendations for field action to prevent failure. For example, field inspection data of critical flaws can be transmitted to the office instantly via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Finally, we note that the variance formula given by Ku [79] and used in this paper to derive the risk uncertainty formula has also been applied by Fong and his colleagues [82][83][84][85] in estimating uncertainty in fatigue life prediction or failure probability due to a number of source uncertainties such as:…”
Section: Discussionmentioning
confidence: 95%
“…Finally, we note that the variance formula given by Ku [79] and used in this paper to derive the risk uncertainty formula has also been applied by Fong and his colleagues [82][83][84][85] in estimating uncertainty in fatigue life prediction or failure probability due to a number of source uncertainties such as:…”
Section: Discussionmentioning
confidence: 95%
“…In a 2008 PVP conference paper by Fong, Hedden, Filliben, and Heckert [32], a prototype web-based NDE data analysis methodology to estimate the reliability of weld flaw detection, location, and sizing was described with an example application to the 1968 ultrasonic testing (UT) data of weld seam in PVRC test block 251J and the 1984 sectioning data of the same block implanted with 15 flaws of 4 types.…”
Section: Isi and Nde Database Db-2mentioning
confidence: 99%
“…In that 2008 example [32], five factors were identified as potential contributors of uncertainty to the UT process of Team A in finding an implanted 2-inch crack. Figures 10 and 11, the resulting analysis using judgment-based fictitious data concluded that the UT operator's experience (X1) and the transducer probe angle (X4) are the two dominant factors contributing to the uncertainty of the Team A's UT results.…”
Section: Isi and Nde Database Db-2mentioning
confidence: 99%
See 2 more Smart Citations